2016
DOI: 10.1103/physrevd.93.083507
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic influence on inflationary fluctuations

Abstract: Motivated by apparent persistent large scale anomalies in the CMB we study the influence of fermionic degrees of freedom on the dynamics of inflaton fluctuations as a possible source of violations of (nearly) scale invariance on cosmological scales. We obtain the non-equilibrium effective action of an inflaton-like scalar field with Yukawa interactions (Y D,M ) to light fermionic degrees of freedom both for Dirac and Majorana fields in de Sitter space-time. The effective action leads to Langevin equations of m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(84 citation statements)
references
References 133 publications
5
79
0
Order By: Relevance
“…A Yukawa coupling between the inflaton fluctuations and fermionic fields yields an influence action in terms of self-energy and noise kernels much in the same manner as for the case studied in the previous sections. Results of this study will be reported elsewhere [63].…”
Section: Discussionmentioning
confidence: 99%
“…A Yukawa coupling between the inflaton fluctuations and fermionic fields yields an influence action in terms of self-energy and noise kernels much in the same manner as for the case studied in the previous sections. Results of this study will be reported elsewhere [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this reference the equivalence between integrating out the heavy (or short wavelength) degrees of freedom in the path integral representation and the quantum master equation is established up to second order in the coupling. This equivalence and the relation to a stochastic description translate directly to the case of an FRW cosmology, these more formal aspects are relegated to a companion article [44]. In this article we obtain the quantum master equation directly and apply it to understand several physical consequences.…”
Section: Quantum Master Equationmentioning
confidence: 99%
“…[43] it is shown that this approximation results from obtaining the non-equilibrium effective action in the path integral SchwingerKeldysh formulation in a consistent cumulant expansion of the trace over the environmental degrees of freedom when the initial density matrix is factorized. These aspects translate directly to an FRW cosmology in conformal time as discussed in a companion article [44]. In this article we assume (as is common in the literature) that the initial density matrix at the beginning of inflation is of the factorized form, it is clearly interesting to consider the case of initial correlations, which is postponed to further study.…”
Section: Quantum Master Equationmentioning
confidence: 99%
“…1 Second, open relativistic QFTs are very relevant by themselves in heavy ion physics [19][20][21][22] and cosmology [23][24][25][26][27][28][29][30]. Third motivation is to better understand the apparently non-unitary evolution engendered by black holes and to give a quantitative characterization of the information loss.…”
Section: Jhep11(2017)204mentioning
confidence: 99%